Odontaster validus Koehler 1905 ... - Jangoux, Michel (Zenodo, 2022)
validus Koehler, 1905, Odontaster Odontaster validus Koehler, 1905: 467; 1906: 6, pl. 3, figs 22-26. — Clark 1993: 198. CURRENT STATUS. — Odontaster validus Koehler, 1905. TYPE MATERIAL. — Antarctic • 1 syntype; Booth-Wandel Island; French Antarctic expedition (1903-1905); MNHN-IE-2014-190 • 1 syntype; same as for preceding; MNHN-IE-2014-208 • 1 syntype; Biscoe Bay; same as for preceding; MNHN-IE-2014-397 • 1 syntype; unspecified locality; same as for preceding; MNHN-IE-2014-210 • 1 syntype; same as for preceding; MNHN-IE-2014-212 • 1 syntype; same as for preceding; MNHN-IE-2014-216 • 1 syntype; same as for preceding; MNHN-IE-2014-230. REMARK Koehler (1906) mentioned ten specimens originating from Anvers Island (3), Both-Wandel Island (2), Biscoe Bay (3), Flanders’ Bay (1), and unspecified locality (1). ... : Published as part of Jangoux, Michel, 2022, The type specimens of extant asteroids (Echinodermata) in the Muséum national d'Histoire naturelle of Paris, pp. 259-334 in Zoosystema 44 (11) on page 322, DOI: 10.5252/zoosystema2022v44a11, http://zenodo.org/record/6616817 ...